Inovasi Pelayanan Administrasi Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Luwu Timur - Astuti, Puji; Setiawati, Budi; Malik, Ihyani (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aimed to describe innovative services in the Department of Population and Civil Administration of East Luwu Regency, by looking at how the relative benefits, suitability, complexity, possibilities and convenience provided to the community after the many new innovations that arose. This study used qualitative research with phenomenology type and the technique used purposive sampling to determine informants. The results of this study showed that only a few innovations were running normally, such as face to face service innovation implemented in the Office, relying on KTP-el, making online population documents, traveling services and on the street services which were new programs this year. Many obstacles were faced, such as the lack of human resources who understood technology, information and communication, many tools that required rejuvenation and uncertainty in the budget. In addition, the paradigm of society which was still traditional in nature was a challenge in changing people's views in facing technological advances, information and communication at this time.